Epidemiología de los desórdenes venosos crónicos y factores asociados en amerindios nativos embera-chamí, Antioquia (2019)
ABSTRACT: To analyze the prevalence of chronic venous disorders (CVD) in the embera-chamí from Cristianía (Karmata Rua), in the southwest of Antioquia, and to study posible associated factors (AF). Methodology: A cross sectional study of a random sample of 488 subjects. The diagnosis was performed through Doppler ultrasonography. Information about sociodemographic, behavioral and anthropometric AFs was collected. The most relevant AFs were selected through multiple binary logistic regression. Results: The prevalence of varicose veins was 27.5% and that of chronic venous insufficiency (cvi) was 0.8%. Superficial anatomical segments were compromised in 34.8% of individuals. Age was the most important AF, with an Odds Ratio (OR) between 3.33 and 6.30 according to the type of cvd. Being a female, parity, fat in the thigh/leg and large size were associated with telangiectasias. Age, abdominal fat and leg shape were AF of varicose veins. Superficial veins in both sexes were associated with age and abdominal fat and in women, also with a family background of varicose veins. Deep and perforator veins were associated with age and peripheral fat depletion. Conclusions: The low prevalence pattern of CVDs in embera-chamí may be a consequence of lifestyles involving daily physical activity and genetic differences shared with Amerindians. Deep and perforating disorders should be considered in differential health care programs in relation to mestizos. Keywords: chronic venous disorders, varicose veins, telangiectasias, chronic venous insufficiency, Amerindians, embera-chamí.